Liquid chromatography applications - Fanali, Salvatore (Handbooks in separation science, 2023)
"Liquid Chromatography: Applications, Third Edition delivers a single source of authoritative information on all aspects of the practice of modern liquid chromatography. The text gives those working in academia and industry the opportunity to learn, refresh, and deepen their understanding of the field by covering basic and advanced theoretical concepts, recognition mechanisms, conventional and advanced instrumentation, method development, data analysis, and more. This third edition addresses new developments in the field with updated chapters from expert researchers. The book is a valuable reference for research scientists, teachers, university students, industry professionals in research and development, and quality control managers."